Kesiapan Orang Tua dalam Menghadapi Sibling Rivalry pada Anak Usia Toddler - Wahyu, Wiwik; Widyaningsih, Tri Sakti; Aini, Khusnul (Jurnal Ners Widya Husada, 2017)
Penggunaan Nasogatric Tube merupakan salah satu faktor terjadinya pneumonia. Pneumonia merupakan proses inflamasi pada parenkim paru yang biasanya berhubungan dengan peningkatan cairan alveolar dan interstisial. Pneumonia adalah infeksi nosokomial tertinggi ke dua angka kejadiannya. Komplikasi penggunaan nasogatric tube dapat mengakibatkan pneumonia aspirasi. Penelitian kuantitatif dengan jenis observasional analitik dan menggunakan rancangan cross sectional. Pengambilan sampel dengan tekhnik consecutive sampling  dengan jumlah sampel sebanyak 17 responden. Responden yang diambil adalah responden yang menggunakan NGT >48 jam. Pengumpulan data menggunakan lembar observasi. Analisis ini menggunakan uji statistik Fisher Exact. Ditemukan kejadian pneumonia sebanyak 13 orang (76,5%). Berdasarkan uji statistik fisher exact didapatkan hasil p value 0,022 < α= 0,05.dan OR = 0,028. Ada hubungan penggunaan nasogatric tube dengan terjadinya pneumonia. Kata kunci: penggunaan nasogatric tube, terjadinya pneumonia PARENTS READINESS IN FACING SIBLING RIVALRY IN TODDLER AGE CHILDREN ABSTRACTSibling rivalry is a competition, jealousy and anger between siblings. Preparedness with parental behavior may affect the occurrence of sibling rivalry in children of toddler. Phenomenon Occurring In Crewek Village District Kradenan Grobogan district there are mothers who scolded his son for fighting each other and some who twisted the ear, pinch or blame his eldest son. This study aims to determine the relationship of preparedness with the behavior of parents in the face of sibling rivalry in children aged toddler. The type of research was quantitative with cross sectional approach with total sampling sampling technique conducted on 35 parents who had children aged 1-3 years in May 2017. Data collection using preparedness questionnaire and parental behavior. The results showed that the majority of respondents with good readiness 54.3% and negative behavior (60.0%). The result of statistical test using chi square test with α = 0,05 obtained result that there is significant correlation between readiness with parent behavior in Crewek Village, Sub District of Kradenan Grobogan Regency (p value = 0,013) with value X2 = 6,217. There is a relationship of readiness with parental behavior in facing sibling rivalry in toddler-age children in Crewek Village, Kradenan Sub-district, Grobogan District. Keywords: parental readiness, parental behavior, sibling rivalry, toddler.